Multifunctional bionic coating with osteogenic induction and antibiosis functions and preparation method thereof

By preparing bone-imitating porous titanium dioxide nanotube layer and phase-transformation lysozyme layer on titanium alloy implantation material, combining bone-targeting biological molecules to form a multifunctional bionic coating with osteogenesis induction and antibacteriality, titanium alloy transplantation is solved The stress shielding and insufficient antibacterial performance of the materials used in the treatment of osteoarthritis have achieved improvements in osteocyte proliferation and antibacterial effects.

CN119113218APending Publication Date: 2024-12-13HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411151142.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing titanium alloy implant materials have problems such as stress shielding effect, insufficient biological activity and poor antibacterial performance in the repair of bone defects such as osteoarthritis and osteoporosis, resulting in implant failure and early infection.

Method used

Anodizing method is used to prepare bone-imitated porous titanium dioxide nanotube layer, and through the combination of phase transformation lysozyme and bone-targeted biomolecular layer, a multifunctional bionic coating with osteogenesis induction and antibacteriality, including chelating active metals Ion and tetracycline antibiotics extend the release cycle of metal ions, enhance cell adhesion and antibacterial properties.

Benefits of technology

It significantly reduces the elastic modulus of titanium alloy, promotes the proliferation and differentiation of bone cells, improves the interaction between implants and bone tissue, prolongs the release cycle of metal ions, slows down cytotoxicity, and significantly improves antibacterial properties, promotes Early bone integration and reduce the risk of infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113218A_ABST
    Figure CN119113218A_ABST
Patent Text Reader

Abstract

The invention discloses a multifunctional bionic coating with osteogenesis induction and antibiosis functions and a preparation method thereof.The multifunctional bionic coating takes a biomedical material as a substrate and sequentially comprises a bone-imitating porous titanium dioxide nanotube layer, a phase-transition lysozyme nano-protein layer chelated with active metal ions and a bone-targeting biomolecule layer from inside to outside; the preparation method comprises the following steps: preparing a hollow bone-imitating porous titanium dioxide nanotube as a storage chamber on the surface of a biomedical material by adopting an anodic oxidation method, then preparing a phase-transition lysozyme protein layer chelated with active metal ions through in-situ self-assembly, and finally chemically connecting limb bone targeting biomolecules on the surface of the protein layer. And forming a bone targeting biomolecular layer. The multifunctional bionic coating can effectively control release of active metal ions, improve osteoblast activity and induce osteoblast adhesion and hydroxyapatite formation, and also has excellent antibacterial performance; and the preparation method is simple and easy to implement, and has a wide application prospect in the field of bone repair materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a multifunctional bionic coating having both osteogenic induction and antibacterial properties and a preparation method thereof. Background Art

[0002] The repair and treatment of bone defects such as fractures and trauma under the combined complications of osteoarthritis, osteoporosis, and bone tumors are still the main challenges faced by the clinical medical field. Titanium and its alloys have become one of the ideal implant substitute materials for orthopedics and orthopedics due to their high specific strength, excellent corrosion resistance, and reliable biocompatibility. However, the elastic modulus of titanium-based alloys is relatively high, which is extremely mismatched with natural bone tissue, and easily leads to stress shielding effect, thereby aggravating the bone resorption process and causing implant failure; and the naturally passive dense oxide layer spontaneously formed on the surface has no biological activity, which is not conducive to physiological processes such as osteogenic differentiation, adhesion, proliferation and functional expression of osteoblasts, and poor interaction with surrounding human tissues after implantation, resulting in insufficient bone integration; in addition, the weak antibacterial properties also accelerate the early infection of implant surgery and cause inflammation. Therefore, it is urgent to carry out surface modification of biomedical titanium alloys to cope with complex clinical environments, promote early bone integration at the interface between implants and bone tissue, and avoid bacterial infection.

[0003] Human bone is a tissue with a micro-nano multi-level porous structure, which can be used to store a large amount of nutrients, growth factors, and cells, and can also be used for material exchange and transportation. Constructing a bone-like porous material with a nanotube structure on the surface of implanted titanium alloy can significantly reduce the elastic modulus of titanium alloy, and can also realize the storage and transportation of nutrients in the surrounding tissues, and promote rapid vascularization in the bone; the nanostructure also provides more adhesion sites for cell adhesion, which is conducive to the rapid spreading of cells. In addition, the hollow structure also provides a large amount of storage space for the loading and controlled release of bioactive substances. Bones contain a large number of various metal elements, which play an important role in maintaining the steady-state balance of bone tissue, accelerating angiogenesis, regulating bone metabolism, and maintaining the normal functional expression of bone cells. Carrying metal active ions in nanotubes can effectively achieve osteogenic differentiation around the implant site, inhibit osteoclasts, and achieve steady-state regulation of bone tissue. However, metal ions can diffuse rapidly with the surrounding tissue fluid, forming a burst release, which is toxic to cells and tissues. Therefore, the release of metal ions must be effectively controlled.

[0004] However, in the prior art, when preparing functional coatings containing metal ions, it is impossible to achieve controlled release of active metal ions, resulting in rapid failure of the functional coatings and inability to be well applied. In addition, the existing coatings also have shortcomings such as poor antibacterial properties and high cytotoxicity. Summary of the invention

[0005] Purpose of the invention: The first purpose of the present invention is to provide a multifunctional bionic coating having both osteogenic induction and antibacterial properties; the second purpose of the present invention is to provide a method for preparing the above-mentioned multifunctional bionic coating.

[0006] Technical solution: The multifunctional bionic coating with both osteoinduction and antibacterial properties provided by the present invention is based on biomedical materials and includes, from the inside to the outside, a bone-mimicking porous titanium dioxide nanotube layer, a phase-shift lysozyme nanoprotein layer for chelating active metal ions, and a bone-targeted biomolecule layer.

[0007] Furthermore, in the bone-mimicking porous titanium dioxide nanotube layer, the diameter of the porous titanium dioxide nanotube is 10-200 nm, the length is 0.1-20 μm, and it is an amorphous or anatase structure.

[0008] Furthermore, the active metal is one or more of strontium, calcium, zinc, magnesium, cerium, and gallium; and the lysozyme is one or more of egg white lysozyme and human lysozyme.

[0009] Furthermore, the bone-targeted biomolecule is an amino-containing tetracycline-type bone-loving antibiotic; the amino-containing tetracycline-type bone-loving antibiotic is one of tetracycline hydrochloride, doxycycline, minocycline, and tigecycline, preferably tetracycline hydrochloride.

[0010] Furthermore, the biomedical material is titanium and its alloys, including Ti13Nb13Zr, Ti12Mo6Zr, Ti6Al7Nb, and TA2 alloys, which can be used to manufacture prostheses or artificial organs such as artificial joints, fixed bridges, and dental plastic surgery devices implanted in the human body, and can be used in the field of bone repair materials.

[0011] The method for preparing the multifunctional bionic coating having both osteogenic induction and antibacterial properties provided by the present invention comprises the following steps:

[0012] (1) preparing a bone-mimicking porous titanium dioxide nanotube layer on the surface of the pretreated substrate by an anodic oxidation method, thereby obtaining a substrate having a bone-mimicking porous titanium dioxide nanotube layer;

[0013] (2) placing the material obtained in step (1) in a reaction solution formed by mixing a phase-change reducing agent solution and a mixed solution containing an active metal salt, lysozyme, and a solvent, and performing in-situ self-assembly to obtain a matrix having a bone-mimicking porous titanium dioxide nanotube layer and a phase-change lysozyme nanoprotein layer chelating active metal ions;

[0014] (3) The material obtained in step (2) is first placed in a carboxyl activation solution for carboxyl activation, and then a bone-targeting molecule solution is added to the carboxyl activation solution. The bone-targeting molecules are grafted onto the surface of the material through an amide reaction to form a bone-targeting biomolecule layer, thereby finally obtaining a multifunctional bionic coating with both osteoinduction and antibacterial properties.

[0015] Furthermore, in step (1), the pretreatment includes sanding, polishing, cleaning and drying, and the polishing includes mechanical polishing and electrochemical polishing.

[0016] Further, in step (1), the process parameters of the anodization method include: the composition of the electrolyte includes: soluble fluoride, water and organic alcohol solvent, the substrate is used as the anode, the high-purity graphite rod is used as the cathode, the voltage is 10-130V, preferably 40-60V, more preferably 40-50V, the anodization time is 1-180min, preferably 50-80min, more preferably 45-60min, the reaction temperature is 0-50°C, preferably 20-30°C, more preferably 25±2℃, the distance between cathode and anode is 30-60mm, preferably 40-50mm, more preferably 40-45mm; in the electrolyte, the mass percentage concentration of soluble fluoride is 0.1-10wt.%, preferably 0.5wt.%, the volume percentage concentration of water is 2-3vol.%, preferably 2vol.%, the soluble fluoride is ammonium fluoride or hydrofluoric acid, preferably ammonium fluoride, and the organic alcohol solvent is ethylene glycol, glycerol or isopropanol, preferably ethylene glycol.

[0017] Further, in step (2), the phase change reducing agent solution is composed of a phase change reducing agent and a solvent, the phase change reducing agent is tri(2-carboxyethyl)phosphine, the solvent is 4-hydroxyethylpiperazineethanesulfonic acid, the molar concentration of the phase change reducing agent in the phase change reducing agent solution is 10-100mM, preferably 40-60mM, more preferably 50-60mM, the pH of the phase change reducing agent solution is 6.5-7.5, preferably 7±0.2, within this pH range, it is conducive to the rapid phase transition of lysozyme, while other pH values ​​will cause the phase transition lysozyme to fail to form; In the mixed solution, the solvent is 4-hydroxyethylpiperazineethanesulfonic acid, the concentration is 5-30mM, preferably 10-20mM, the pH is 6.9-7.3, preferably 7.2±0.1, the mass concentration of lysozyme in the mixed solution is 1-5mg / mL, preferably 2-3mg / mL, and the molar concentration of the active metal salt in the mixed solution is 0.5-6mM, preferably 1.8-3.5mM; the volume ratio of the phase shift reducing agent solution to the mixed solution is 1:1-2, preferably 1:1; the time of the in situ self-assembly is 1-3h, preferably 2±0.5h.

[0018] Furthermore, in step (3), the activation components in the carboxyl activation solution include 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide, wherein the molar concentration of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride in the carboxyl activation solution is 10-50 mM, preferably 20-40 mM, and the molar concentration of N-hydroxysuccinimide in the carboxyl activation solution is 5-30 mM, preferably 10-20 mM; the time of the carboxyl activation is 1-5 h, preferably 2-4 h; the molar concentration of the bone targeting molecule solution is 2-10 mM, preferably 4-6 mM; and the time of the amide reaction is 10-24 h, preferably 12-16 h.

[0019] Principle of the invention: The present invention prepares bone-mimicking porous titanium dioxide hollow nanotube arrays on the surface of the substrate through anodizing technology, which can reduce the stress shielding effect of medical titanium alloys, increase surface roughness, and provide space and sites for the loading of active substances, storage of nutrients, and adhesion of cells; active metal ions can effectively promote the proliferation and differentiation of osteoblasts, and regulate the expression of related functions and bone homeostasis.

[0020] Lysozyme is composed of a large number of amino acids and contains a large number of chemically active functional groups. Its disulfide bonds undergo a phase transition after being cleaved by the reducing agent tri(2-carboxyethyl)phosphine, and self-assemble to form a starch-like product. This product can not only adhere to the surface of any form of substrate (including nanotubes), but also give the interface more chemically active groups such as amino, carboxyl, and hydroxyl groups, further chelate active metal ions, prolong the ion release cycle, slow down the toxicity of surrounding cells and tissues, and provide active reaction sites for the subsequent chemical grafting of biological functional molecules; in addition, lysozyme also has a certain antibacterial effect.

[0021] Bone-targeted active molecules can induce rapid collagen and mineral deposition, osteogenic differentiation, and osteoblast adhesion and homing around implants in vivo, and mainly include bisphosphonates, oligopeptides, tetracyclines, aptamers, etc. Among them, tetracycline-based bone-targeted active molecules can inhibit matrix metalloproteinase activity, inhibit bone resorption, restore the structure and function of osteoblasts, improve the growth activity of bone tissue under pathological conditions, and restore the normal function of osteoblasts. As a broad-spectrum antibiotic, they have inhibitory effects on bacteria and fungi, thereby reducing the risk of infection in implant surgery. The β-diketone, enol, and formamide groups on the tetracycline structure can form chelate bonds with calcium ions on hydroxyapatite in bone tissue, and the hydroxyl groups on tetracycline can also form van der Waals forces and hydrogen bonds with hydroxyapatite, so they have extremely strong bone affinity, thereby achieving bone targeting. The other end of the tetracycline molecule contains an active amino group, which can be covalently bonded to the carboxyl group on the phase-shift lysozyme activated by 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide through an amide reaction, thereby achieving further grafting of bone-targeted molecules, thereby promoting the induced crystal deposition of hydroxyapatite, collagen formation, and osteoblast adhesion and functional expression under physiological conditions, thereby promoting early bone integration.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The phase-shift lysozyme nanoprotein particle coating used in the present invention is not limited by the substrate material and shape, and can be quickly and autonomously installed on the surface of various materials in situ; (2) The metal ions and bone-targeted active molecules used in the present invention have synergistic osteogenesis and antibacterial effects, and can effectively delay the release cycle through the chelation or covalent action of lysozyme to avoid cell and tissue toxicity caused by sudden release; (3) The titanium dioxide nanotube bone-mimicking porous structure prepared by the present invention can provide a large number of adhesion sites for cell adhesion, and store a large amount of nutrients for bone cell growth, which is beneficial to material exchange and transportation; (4) The conditions required for the preparation scheme of the present invention are mild, do not require special equipment, are simple in process, and are low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a surface scanning electron microscope image of the coating prepared in Example 1 of the present invention;

[0024] Figure 2 This is a cross-sectional scanning electron microscope image of the coating prepared in Example 1 of the present invention;

[0025] Figure 3 This is the distribution diagram of the main elements on the surface of the coating prepared in Example 1 of the present invention;

[0026] Figure 4 This is a comparison chart of ion release behaviors of the coatings prepared in Example 1 of the present invention and Comparative Examples 1 and 2;

[0027] Figure 5 This is a cell fluorescence image (×200) of osteoblasts inoculated on the surface of the coating prepared in Example 1 of the present invention and cultured for 3 days;

[0028] Figure 6 Evaluation of the antibacterial properties of the coating prepared in Example 1 of the present invention;

[0029] Figure 7 This is a surface scanning electron microscope image of the coating prepared in Comparative Example 1;

[0030] Figure 8 This is a cell fluorescence image (×200) of the surface of the coating prepared in Comparative Example 1 inoculated with osteoblasts and cultured for 3 days;

[0031] Fig. 9 This is an evaluation of the antibacterial performance of the coating prepared in Comparative Example 1. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments and drawings.

[0033] Example 1: The multifunctional bionic coating with both osteoinduction and antibacterial properties provided in this example takes TA2 alloy as the matrix, and constructs, from the inside to the outside, a titanium dioxide nano-hollow tube layer (i.e., a bone-mimicking porous titanium dioxide nano-tube layer), a self-assembled lysozyme layer carrying strontium ions (i.e., a phase-change lysozyme nano-protein layer chelating active metal ions), and a tetracycline hydrochloride layer (i.e., a bone-targeted biomolecule layer).

[0034] The preparation process is as follows: TA2 alloy is cut into 70mm×50mm×0.1mm samples, the surface is sanded and polished to a mirror surface, and then ultrasonically cleaned with acetone and ethanol for 30 minutes respectively, and then blown dry. 250mL of organic electrolyte of ethylene glycol + 0.5wt.% ammonium fluoride + 2vol.% deionized water is prepared, the voltage is maintained at 45V, the distance between the cathode and the anode is maintained at 4cm, the oxidation temperature is 25°C, the oxidation time is 60min, after anodic oxidation, the sample is ultrasonically cleaned with deionized water for 30min, and then blown dry to obtain a nanotube sample. A mixed solution of 10mM 4-hydroxyethylpiperazineethanesulfonic acid containing 2mg / mL of egg white lysozyme, 1.8mM strontium acetate, pH=7.2, and a 4-hydroxyethylpiperazineethanesulfonic acid solution containing 50mM tris(2-carboxyethyl)phosphine, pH=7.0 is prepared. The above two solutions were mixed and quickly immersed in the above nanotube sample. After reacting at room temperature for 2 hours, the sample containing the self-assembled lysozyme layer was obtained by rinsing with deionized water and blowing dry. A 20mM (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) and 10mM N-hydroxysuccinimide solution were prepared and immersed in the above sample containing the self-assembled lysozyme layer. After fully activating the carboxyl group for 3 hours, a 4mM tetracycline hydrochloride solution was added and fully reacted for 12 hours. The sample was taken out, ultrasonically cleaned, and air-dried to obtain a multifunctional bionic coating.

[0035] Example 2: The multifunctional bionic coating with both osteoinduction and antibacterial properties provided in this example is based on Ti13Nb13Zr alloy and sequentially constructs a titanium dioxide nano hollow tube layer, a self-assembled lysozyme layer carrying zinc ions, and a tetracycline hydrochloride layer from the inside out.

[0036] The preparation process is as follows: Ti13Nb13Zr alloy is cut into 70mm×50mm×0.1mm samples, the surface is sanded and polished to a mirror surface, and then ultrasonically cleaned with acetone and ethanol for 30 minutes respectively, and then blown dry. 250mL of organic electrolyte of ethylene glycol + 0.5wt.% ammonium fluoride + 2vol.% deionized water is prepared, the voltage is maintained at 50V, the distance between the cathode and the anode is maintained at 4cm, the oxidation temperature is 25℃, the oxidation time is 60min, after anodic oxidation, the sample is ultrasonically cleaned with deionized water for 30min, and then blown dry to obtain a nanotube sample. A mixed solution of 20mM 4-hydroxyethylpiperazineethanesulfonic acid containing 2mg / mL lysozyme and 1.8mM zinc sulfate, pH=7.2, and a 4-hydroxyethylpiperazineethanesulfonic acid solution containing 50mM tris(2-carboxyethyl)phosphine, pH=7.0 is prepared. The above two solutions were mixed and quickly immersed in the above nanotube sample. After reacting at room temperature for 2 hours, the sample containing the self-assembled lysozyme layer was obtained by rinsing with deionized water and blowing dry. A 20mM (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) and 10mM N-hydroxysuccinimide solution were prepared and immersed in the above sample containing the self-assembled lysozyme layer. After fully activating the carboxyl group for 3 hours, a 4mM tetracycline hydrochloride solution was added and fully reacted for 12 hours. The sample was taken out, ultrasonically cleaned, and air-dried to obtain a multifunctional bionic coating.

[0037] Example 3: The multifunctional bionic coating with both osteoinduction and antibacterial properties provided in this example is based on Ti12Mo6Zr alloy and sequentially constructs a titanium dioxide nano hollow tube layer, a self-assembled lysozyme layer carrying magnesium ions, and a doxycycline layer from the inside out.

[0038] The preparation process is as follows: Ti12Mo6Zr alloy is cut into 70mm×50mm×0.1mm samples, the surface is sanded and polished to a mirror surface, and then ultrasonically cleaned with acetone and ethanol for 30 minutes respectively, and then blown dry. 250mL of organic electrolyte of ethylene glycol + 0.5wt.% ammonium fluoride + 2vol.% deionized water is prepared, the voltage is maintained at 40V, the distance between the cathode and the anode is maintained at 4.5cm, the oxidation temperature is 25℃, the oxidation time is 45min, after anodic oxidation, the sample is ultrasonically cleaned with deionized water for 30min, and then blown dry to obtain a nanotube sample. A mixed solution of 20mM 4-hydroxyethylpiperazineethanesulfonic acid containing 3mg / mL lysozyme, 1.8mM MgSO4, pH=7.2, and a 4-hydroxyethylpiperazineethanesulfonic acid solution containing 60mM tris(2-carboxyethyl)phosphine, pH=7.0 is prepared. The above two solutions were mixed and quickly immersed in the above nanotube sample. After reacting at room temperature for 2 hours, the sample containing the self-assembled lysozyme layer was obtained by rinsing with deionized water and blowing dry. A 20Mm (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) and 10mM N-hydroxysuccinimide solution were prepared and immersed in the above sample containing the self-assembled lysozyme layer. After fully activating the carboxyl group for 3 hours, a 4mM doxycycline solution was added and fully reacted for 12 hours. The sample was taken out, ultrasonically cleaned, and air-dried to obtain a multifunctional bionic coating.

[0039] Example 4: The multifunctional bionic coating with both osteoinduction and antibacterial properties provided in this example uses TA2 alloy as a matrix, and sequentially constructs a titanium dioxide nano hollow tube layer, a self-assembled lysozyme layer carrying strontium ions, and a tigecycline layer from the inside out.

[0040] The preparation process is as follows: TA2 alloy is cut into 70mm×50mm×0.1mm samples, the surface is sanded and polished to a mirror surface, and then ultrasonically cleaned with acetone and ethanol for 30 minutes respectively, and then blown dry. 250mL of organic electrolyte of ethylene glycol + 0.5wt.% ammonium fluoride + 2vol.% deionized water is prepared, the voltage is maintained at 45V, the distance between the cathode and the anode is maintained at 4cm, the oxidation temperature is 25℃, the oxidation time is 60min, after anodic oxidation, the sample is ultrasonically cleaned with deionized water for 30min, and then blown dry to obtain a nanotube sample. A mixed solution of 10mM 4-hydroxyethylpiperazineethanesulfonic acid containing 3mg / mL lysozyme, 1.8mM strontium acetate, pH 7.2, and a 4-hydroxyethylpiperazineethanesulfonic acid solution containing 60mM tris(2-carboxyethyl)phosphine, pH=7.0 is prepared. The above two solutions were mixed and quickly immersed in the above nanotube sample. After reacting at room temperature for 2 hours, the sample containing the self-assembled lysozyme layer was obtained by rinsing with deionized water and blowing dry. 20mM (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) and 10mM N-hydroxysuccinimide solution were prepared, and the sample containing the self-assembled lysozyme layer was immersed in it. After fully activating the carboxyl group for 3 hours, 4mM tigecycline solution was added and fully reacted for 12 hours. The sample was taken out, ultrasonically cleaned, and air-dried to obtain a multifunctional bionic coating.

[0041] Comparative Example 1: The difference from Example 1 is that the self-assembled lysozyme layer carrying strontium ions and the tetracycline hydrochloride layer are not included.

[0042] The preparation process is as follows: TA2 alloy is cut into 70mm×50mm×0.1mm samples, the surface is sanded and polished to a mirror surface, and then ultrasonically cleaned with acetone and ethanol for 30 minutes respectively, and then blown dry. 250mL of organic electrolyte of ethylene glycol + 0.5wt.% ammonium fluoride + 2vol.% deionized water is prepared, the voltage is maintained at 45V, the distance between the cathode and the anode is maintained at 4cm, the oxidation temperature is 25°C, the oxidation time is 60min, after anodization, the sample is ultrasonically cleaned with deionized water for 30min, and then blown dry to obtain a nanotube sample. A 1.8mM strontium acetate solution is used to immerse the nanotube sample in the strontium acetate solution, and it is taken out after 2h, and the surface is rinsed with deionized water and blown dry to obtain the coating of Comparative Example 1.

[0043] Comparative Example 2: The difference from Example 1 is that no tetracycline hydrochloride layer is included.

[0044] The preparation process is as follows: TA2 alloy is cut into 70mm×50mm×0.1mm samples, the surface is sanded and polished to a mirror surface, and then ultrasonically cleaned with acetone and ethanol for 30 minutes respectively, and then blown dry. 250mL of organic electrolyte of ethylene glycol + 0.5wt.% ammonium fluoride + 2vol.% deionized water is prepared, the voltage is maintained at 45V, the distance between the cathode and the anode is maintained at 4cm, the oxidation temperature is 25°C, the oxidation time is 60min, after anodic oxidation, the sample is ultrasonically cleaned with deionized water for 30min, and then blown dry to obtain a nanotube sample. A mixed solution of 10mM 4-hydroxyethylpiperazineethanesulfonic acid containing 2mg / mL of egg white lysozyme, 1.8mM strontium acetate, pH 7.2, and 50mM 4-hydroxyethylpiperazineethanesulfonic acid solution of tris(2-carboxyethyl)phosphine, pH=7.0 is prepared. The two solutions were mixed and quickly immersed into the nanotube sample. After reacting at room temperature for 2 hours, the sample was rinsed with deionized water and then dried to obtain the coating of Comparative Example 2.

[0045] The coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were characterized and tested for biocompatibility. The results are shown in the attached Figure 1-Figure 9 shown.

[0046] Figure 1 The surface morphology of the self-assembled lysozyme loaded with strontium ions and grafted with tetracycline hydrochloride bone targeting molecules prepared in Example 1. Figure 1 As shown, the prepared phase transition lysozyme particles have a size of about 200-300 nm, and the lysozyme particles adhere to each other and cover the surface of the titanium dioxide nanotubes with an inner diameter of about 50-70 nm.

[0047] Figure 2 The cross-sectional morphology of the self-assembled lysozyme loaded with strontium ions and grafted with tetracycline hydrochloride bone targeting molecules prepared in Example 1. Figure 2 As shown, the outer diameter of the nanotube is about 100 nm and the tube length is about 4-5 μm.

[0048] Figure 3 This is the surface element distribution diagram of the self-assembled lysozyme loaded with strontium ions and grafted with tetracycline hydrochloride bone targeting molecules on the surface of the nanotube prepared in Example 1. Figure 3 As shown in the figure, the surface of the nanotube is composed of elements such as Ti, O, C, Sr, N and S. The Ti element comes from the nanotube; the O element mainly comes from the nanotube, the phase-shift lysozyme and the tetracycline hydrochloride molecules, and may also contain adsorbed water vapor; the C element comes from the phase-shift lysozyme and tetracycline hydrochloride, and may also contain organic pollutants adsorbed on the surface; the Sr element comes from the carried strontium ions; the N element comes from the phase-shift lysozyme and tetracycline hydrochloride; and the S element comes from the phase-shift lysozyme.

[0049] Figure 4The metal ion release behavior of the coatings prepared in Example 1 and Comparative Examples 1 and 2 in 14 days (336 hours). Figure 4 As shown, the strontium ion release rate of Example 1 is very slow, and can be continuously released within 336 hours; while Comparative Examples 1 and 2 both show obvious large-scale burst release in the first 24 hours.

[0050] Figure 5 The surface of the nanotube prepared in Example 1 was loaded with strontium ions and self-assembled lysozyme and grafted with tetracycline hydrochloride bone targeting molecular coating. 0.5 mL of mouse embryonic osteoblast precursor cells (MC3T3-E1, 5×10 4 Cells were cultured in 1 mL of complete medium (89% α-MEM medium, 10% fetal bovine serum and 1% penicillin-streptomycin) and 37°C, 5% CO2 humidified environment for 3 days, and then stained with 200 μL of rhodamine (10 μg / mL, PBS as solvent) and 200 μL of DAPI (500 ng / mL, PBS as solvent) for 20 min in the dark to obtain cell fluorescence images. Figure 4 As shown, a large number of cells adhered to the coating surface in a spreading morphology, indicating that the coating can significantly promote the adhesion of osteoblasts.

[0051] Figure 6 The surface of the nanotube prepared in Example 1 was loaded with strontium ions and self-assembled lysozyme and grafted with tetracycline hydrochloride bone-targeting molecular coating. The bacterial colonies were detected by flat-plate coating method. The density of the inoculated Staphylococcus aureus was 5×10 4 CFU / mL. Figure 5 As shown, there is almost no bacterial colony residue on the coating surface, indicating that the coating exhibits excellent antibacterial properties.

[0052] Figure 7 This is a surface morphology of the coating prepared in Comparative Example 1. Figure 7 As shown, the inner diameter of the nanotube is about 60-80nm, the outer diameter is about 100-120nm, and the wall of the nanotube is rough, indicating that metal ions are carried therein.

[0053] Figure 8 For comparative example 1, 0.5 mL of mouse embryonic osteoblast precursor cells (MC3T3-E1, 5×10 4 Cell fluorescence images after culturing for 3 days at 37°C and 5% CO2 in a humidified environment. Figure 8 As shown, the number of surface cells is significantly less than that in Example 1.

[0054] Fig. 9The surface of the coating in comparative example 1 was coated with a flat plate to detect the colony of bacteria with antibacterial properties. Fig. 9 As shown, the number of Staphylococcus aureus colonies on the coating surface is relatively large, and the antibacterial performance is poor compared with that of Example 1 of the present invention.

[0055] The multifunctional coatings prepared in Examples 2 to 4 have the same parameters as those in Example 1, such as the inner diameter, outer diameter, tube length, etc. of the nanotubes and the size of the lysozyme particles. Figure 1 and 2 The number of osteoblasts adhering to the multifunctional coating surface is large, and the morphology is in a spreading state, which is similar to that of Example 1. Figure 5 The results are similar, indicating that the active metal ions released by the multifunctional coating and the surface phase transition lysozyme are beneficial to the growth of osteoblasts, showing good cell growth behavior; the antibacterial property of the multifunctional coating was detected by the flat plate coating method, and the results showed that there were almost no obvious colonies, achieving a good antibacterial effect, and the results were consistent with those of Example 1. Figure 6 resemblance.

Claims

1. A multifunctional biomimetic coating with both osteoinduction and antibacterial properties, based on biomedical materials, characterized by: From the inside to the outside, it includes a bone-mimicking porous titanium dioxide nanotube layer, a phase-transition lysozyme nanoprotein layer that chelates active metal ions, and a bone-targeted biomolecule layer.

2. The multifunctional biomimetic coating according to claim 1, characterized in that: In the bone-mimicking porous titanium dioxide nanotube layer, the porous titanium dioxide nanotubes have a diameter of 10-200 nm and a length of 0.1-20 μm, and are in an amorphous or anatase structure.

3. The multifunctional biomimetic coating according to claim 1, characterized in that: The active metal is one or more of strontium, calcium, zinc, magnesium, cerium, and gallium; and the lysozyme is one or more of egg white lysozyme and human lysozyme.

4. The multifunctional biomimetic coating according to claim 1, characterized in that: The bone-targeting biological molecule is an amino-containing tetracycline-type bone-loving antibiotic.

5. The multifunctional biomimetic coating according to claim 4, characterized in that: The amino-containing tetracycline-type bone-loving antibiotic is one of tetracycline hydrochloride, doxycycline, minocycline, and tigecycline.

6. The multifunctional biomimetic coating according to claim 1, characterized in that: The biomedical material is titanium and its alloys, including Ti13Nb13Zr, Ti12Mo6Zr, Ti6Al7Nb, and TA2 alloy.

7. A method for preparing the multifunctional bionic coating having both osteogenic induction and antibacterial properties according to claim 1, characterized in that: The following steps are involved: (1) preparing a bone-mimicking porous titanium dioxide nanotube layer on the surface of the pretreated substrate by an anodic oxidation method, thereby obtaining a substrate having a bone-mimicking porous titanium dioxide nanotube layer; (2) placing the material obtained in step (1) in a reaction solution formed by mixing a phase-shift reducing agent solution and a mixture containing an active metal salt, lysozyme, and a solvent, and performing in situ self-assembly to obtain a matrix having a bone-mimicking porous titanium dioxide nanotube layer and a phase-shift lysozyme nanoprotein layer chelating active metal ions; (3) The material obtained in step (2) is first placed in a carboxyl activation solution for carboxyl activation, and then a bone-targeting molecule solution is added to the carboxyl activation solution. The bone-targeting molecules are grafted onto the surface of the material through an amide reaction to form a bone-targeting biomolecule layer, and finally a multifunctional biomimetic coating with both osteoinduction and antibacterial properties is obtained.

8. The preparation method according to claim 7, characterized in that In step (1), the process parameters of the anodizing method include: the composition of the electrolyte includes: soluble fluoride, water and organic alcohol solvent, the substrate is used as the anode, the high-purity graphite rod is used as the cathode, the voltage is 10-130V, the anodizing time is 1-180min, the reaction temperature is 0-50°C, and the distance between the cathode and the anode is 30-60mm; in the electrolyte, the mass percentage concentration of the soluble fluoride is 0.1-10wt.%, the volume percentage concentration of water is 2-3vol.%, the soluble fluoride is ammonium fluoride or hydrofluoric acid, and the organic alcohol solvent is ethylene glycol, glycerol or isopropyl alcohol.

9. The preparation method according to claim 7, characterized in that In step (2), the phase shift reducing agent solution is composed of a phase shift reducing agent and a solvent, the phase shift reducing agent is tris(2-carboxyethyl)phosphine, the solvent is 4-hydroxyethylpiperazineethanesulfonic acid, the molar concentration of the phase shift reducing agent in the phase shift reducing agent solution is 10-100mM, and the pH is 6.5-7.5; in the mixed solution, the solvent is 4-hydroxyethylpiperazineethanesulfonic acid, the mass concentration of lysozyme in the mixed solution is 1-5mg / mL, and the molar concentration of the active metal salt in the mixed solution is 0.5-6mM; the volume ratio of the phase shift reducing agent solution to the mixed solution is 1:1-2; and the time of the in situ self-assembly is 1-3h.

10. The preparation method according to claim 7, characterized in that In step (3), the activation components in the carboxyl activation solution include 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, wherein the molar concentration of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride in the carboxyl activation solution is 10-50 mM, and the molar concentration of N-hydroxysuccinimide in the carboxyl activation solution is 5-30 mM; the time for the carboxyl activation is 1-5 hours; the molar concentration of the bone-targeting molecule solution is 2-10 mM; and the time for the amide reaction is 10-24 hours.

Citation Information

Cited By

  • Titanium alloy implant surface bionic coating and preparation method thereof

    CN120267898A

  • Bionic reticular nanofiber composite coating as well as preparation method and infectious bone defect repair application thereof

    CN121338108A